Interconection and Local Wisdom of Malay and Arabs Ulamas Works: Study on Malay and Arabic Manuscripts’ Papers - Fakhriati Fakhriati (Al-Qalam, 2018)
Malay and Arabs are two continents, located in different area, Southeast Asia and Middle East. Historically, writers as ulamas (religious prominent figures) tended to use watermarked papers for writing many things both related to religious, historical knowledge, and also their experience. Looking at the manuscripts existing nowadays, almost all Malay and Arabic manuscripts’ papers have unique and similar watermark images and countermark inside. It cannot be denied that historical background and context appeared behind the papers. Historically, the relationship among the countries since the coming of Islam to Malay -- that was in Aceh at the first -- gave the effect of produced and using the papers. Trade and diplomatic relation can be assumed as the biggest factor taken places in this aspect. Besides, Western countries also took important role in exporting their paper to other countries. In addition, they had colonized some Muslims countries both Southeast Asian and Middle East. As the most popular producers of watermark images, Western countries also exported their papers to other countries, including their colonized countries. This paper tries to elaborate ulamas’ paper in these two nations in its similarity and diversity to find local wisdom inside. Thereafter, to analyze the relationship among the countries is another focus of this paper. This paper tries to use Philological, codicological, and socio-historical approach in dealing with the content and physics of the manuscripts, and its historical context.